Friday
March 24, 2017

Post a New Question

Posted by on .

srry i put add instead of subtract srry this is wat i ment 2 put

4x-(9-3x)=8x-1
4x-9-3x=8x-1
3x
1x-9=8x-1
-1x
-9=7x-1
(-9)
7x=8
1.1428571

  • math - , Wednesday, January 12, 2011 at 6:16pm

    4x-(9-3x)=8x-1
    4x - 9 + 3x = 8x - 1
    7x - 9 = 8x - 1
    -x = 8
    x = -8

  • math - , Wednesday, January 12, 2011 at 6:18pm

    o ok thx

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question